Prevalence of traumatic brain injury and epilepsy among prisoners in France: Results of the Fleury TBI study. (20th March 2016) - Durand, E.; Watier, L.; Fix, M.; Weiss, J. J.; Chevignard, M.; Pradat-Diehl, P.
Abstract: Objective : The first aim of this study was to estimate the prevalence of TBI and epilepsy in a French prison population and to study variables known to be associated with TBI. The second aim was to compare prisoners with and without a history of TBI. Participants : All offenders (females, males and juveniles) admitted consecutively to Fleury-Mérogis prison over a period of 3 months were included in the study. Design : During the admission procedure, offenders were interviewed by healthcare staff using a self-reported questionnaire. Results : In all, 1221 prisoners were included. The rates of TBI and epilepsy were high, with a prevalence of 30.6% and 5.9%, respectively. Psychiatric care, anxiolytic and antidepressant treatment, use of alcohol and cannabis were all significantly higher among offenders with a history of TBI. Moreover, the number of times in custody and the total time spent in jail over the preceding 5 years were significantly higher among offenders with a history of TBI. Conclusions : These results provide further evidence that specific measures need to be developed such as, first of all, screening for TBI upon arrival in prison.